(untitled) (Philology, 2026)
The article presents an analysis of a set of cognate verbs with consonant-final roots, which belong to different conjugations in Danish, Swedish and the Bokmål written standard of the Norwegian language. It examines the influence of the phonological characteristics of the verb stems on the types of correspondences between the conjugations. From a diachronic perspective, a comparison with the conjugation of the verbs in question in Old Norse is used to determine the nature and the extent of the changes in the distribution of the verbs between the conjugations in the three languages.